Comparative Evaluation of Macro Minerals Status in Serum of Diabetes Mellitus Patients and Healthy Individuals - Ahmad, Muhammad; Farzana Hakim; Rabia Parveen; Sana; Ayesha Rafiq; Muhammad Iqbal (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare Vitamin B12, Vitamin D, Zinc, Calcium, Sodium, Potassium, Folate, Magnesium and Phosphate levels in Diabetes mellitus patients on oral hypoglycemics (OHG) with healthy population Study Design: Comparative cross sectional study Place and Duration of Study: Outdoor Patient Department, Pak Emirates Military Hospital Rawalpindi, Pakistan from Jan to Dec 2024 Methodology: Patients were selected into Group-1 (diabetic) and Group-2 (non-diabetic) according to inclusion and exclusion criteria using non-probability consecutive sampling method. A questionnaire drafted to collect additional information from patients about demographics and treatment being taken was used. Blood samples were collected on spot for Vitamin B12, Vitamin D, Zinc, Calcium, Sodium, Potassium, Folate, Magnesium, Phosphate and HbA1C levels. WHO classification of Diabetes mellitus was taken as case definition of Diabetes mellitus for Group-1 while persons who did not have the Diabetes mellitus (type-2) were enrolled as non-diabetic cases for Group-2. Comparison of the vitamin and mineral parameters between two groups was done using independent sample t-test and Mann Whitney U test for respective sample types at a p-value of <0.05 as significant. Result: p values of Vitamin B12 and Zinc were significant between Group-1 and Group-2 while insignificant for other minerals and vitamins studied. Conclusion: Patients with Diabetes mellitus on treatment have significantly low Vitamin B12 and Zinc values in comparison to healthy population